Multifunctional nanocomposite hollow fiber membranes by solvent transfer induced phase separation. Issue 1 (December 2017) - Haase, Martin; Jeon, Harim; Hough, Noah; Kim, Jong; Stebe, Kathleen; Lee, Daeyeon
Abstract The decoration of porous membranes with a dense layer of nanoparticles imparts useful functionality and can enhance membrane separation and anti-fouling properties. However, manufacturing of nanoparticle-coated membranes requires multiple steps and tedious processing. Here, we introduce a facile single-step method in which bicontinuous interfacially jammed emulsions are used to form nanoparticle-functionalized hollow fiber membranes. The resulting nanocomposite membranes prepared via solvent transfer-induced phase separation and photopolymerization have exceptionally high nanoparticle loadings (up to 50 wt% silica nanoparticles) and feature densely packed nanoparticles uniformly distributed over the entire membrane surfaces. These structurally well-defined, asymmetric membranes facilitate control over membrane flux and selectivity, enable the formation of stimuli responsive hydrogel nanocomposite membranes, and can be easily modified to introduce antifouling features. This approach forms a foundation for the formation of advanced nanocomposite membranes comprising diverse building blocks with potential applications in water treatment, industrial separations and as catalytic membrane reactors. Coating porous membranes with nanoparticles can enhance their separation and antifouling properties, but methods to do so remain complex. Here, Lee and colleagues use solvent transfer-induced phase separation to prepare nanoparticle-functionalized hollow fiber membranes from bicontinuous interfacially jammed emulsion gels.